KAJIAN TEKNIS TERHADAP HELIPORT BALAI PENDIDIKAN PELATIHAN DAN PEMBENTUKAN KARAKTER SDM TRANSPORTASI (BP3KSDMT) CIWIDEY - Rudy; Moch. Budi Kuntjoro (Langit Biru: Jurnal Ilmiah Aviasi, 2020)
According to Annex 14 Aerodrome,Volume II Amandement 6 November 2014 Heliport, heliport defines as “An aerodrome or a defined area on a structure intended to be used wholly or in part for the arrival, departure and surface movement of helicopters”. Other term we daily used is Helipad, Although in formal regulation this term is not used. In daily understanding Helipad is a part of Heliport, in other word heliport consist of some of helipads. An outline of this research will discuss about real condition of BP3K SDMT Ciwidey Heliport technically,. Is the heliport has been appropriate with current technical specification according to Indonesia regulations ? , Is the permissions problems has been done administratively and things related to manual and procedures has been comply with Air Traffic Services Manual implemented for Surface Heliport like the facility built in this training